SUPPORT OF DECISION MAKING ON THE POSSIBILITY OF THE PROVISION OF EXTRACORPOREAL FERTILIZATION - HNATCHUK, YELIZAVETA; KAPUSTIAN, MARIIA; CHERNETSKA, VIKTORIYA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Abstract – The possibility of having a child is an important indicator of the reproductive health of the population. 10-15% of Ukrainian families are infertile. Most of them resort to the use of assisted reproductive technologies, which are currently developing rapidly in Ukraine. Today in Ukraine there is a need to automate decision-making processes on the possibility of providing extracorporeal fertilization, which can significantly increase the correctness of the contract in terms of civil and medical law. A conducted review and analysis of known decision support systems for the medical field showed the unsuitability of known systems to support decision-making on the possibility of providing extracorporeal fertilization. Therefore, the purpose of this study is to support decision-making on the possibility of extracorporeal fertilization.This paper develops the concept of the decision-making process on the possibility of providing extracorporeal fertilization. The result is a conclusion on the correctness or incorrectness of the content of the contract for extracorporeal fertilization, as well as a recommendation on the conclusion of the contract (in case of the correctness of its content) or revision of the contract (in case of incorrect content). In case of incorrect content of the contract, a hint is given regarding the missing essential conditions and it is proposed to supplement the contract with the missing essential conditions.Promising areas of work of future authors are the formation of an ideal ontology, which contains all the necessary essential conditions for concluding a contract, as well as the implementation of an intelligent agent to support decision-making on extracorporeal fertilization based on civil law.
Keywords: extracorporeal fertilization; contract for the provision of extracorporeal fertilization; civil law regulation; decision making